2000
DOI: 10.1034/j.1399-3003.2000.016003391.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily respiratory mortality and PM10 pollution in Mexico City: importance of considering place of death

Abstract: Daily respiratory mortality and PM10 pollution in Mexico City: importance of considering place of death. M.M. Te Âllez-Rojo, I. Romieu, S. Ruiz-Velasco, M-A. Lezana, M. Herna Ândez-Avila. #ERS Journals Ltd 2000. ABSTRACT: Significant associations have been reported between particles with a 50% cut-off aerodynamic diameter of 10 mm (PM10) and ozone ambient concentrations, and daily number of deaths from respiratory causes. The aim of the present study was to assess such associations among elderly ($65 yrs) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 14 publications
1
37
0
9
Order By: Relevance
“…We read with great interest the recent paper by Tèllez-Rojo et al [1] concerning the importance of considering place of death in daily respiratory mortality related to particles with a 50% cut-off aerodynamic diameter of 10 mm (PM10) pollution in Mexico City. Other studies have reported associations between daily concentrations of PM10 and daily deaths [2].…”
Section: Daily Respiratory Mortality and Pm10 Pollution In Mexico Citymentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the recent paper by Tèllez-Rojo et al [1] concerning the importance of considering place of death in daily respiratory mortality related to particles with a 50% cut-off aerodynamic diameter of 10 mm (PM10) pollution in Mexico City. Other studies have reported associations between daily concentrations of PM10 and daily deaths [2].…”
Section: Daily Respiratory Mortality and Pm10 Pollution In Mexico Citymentioning
confidence: 99%
“…The authors report a significant difference in relative risk (RR) between deaths in medical units and deaths out of medical units for an increase of 10 mg?m -3 in the daily PM10. Tèllez-Rojo et al [1] hypothesized that those who died in medical units had received treatment and been isolated from outdoor pollution. But what was the nature of the association between air pollution and place of death?…”
Section: Daily Respiratory Mortality and Pm10 Pollution In Mexico Citymentioning
confidence: 99%
See 1 more Smart Citation
“…22 En la ciudad de México se han realizado varios análisis de series de tiempo para evaluar este efecto. [23][24][25][26] La figura 2 muestra el comportamiento de la mortalidad en la zona suroeste de la ciudad. Como se puede observar se presenta un componente estacional en el número de muertes, con picos en los meses fríos, de la misma manera que se comporta temporalmente la concentración de material particulado respirable.…”
Section: Análisis Estadístico De Los Estudios Ecológicosunclassified
“…Otras investigaciones han encontrado asociación positiva entre la mortalidad por eventos cardiorespiratorios y enfermedad pulmonar obstructiva con la variación temporal de la concentración de PM 10 y PM 2.5 [14][15][16] . En Santa Marta, Colombia, se encuentran estudios de caracterización de la contaminación que identificaron concentraciones de material particulado en niveles superiores a las establecidas en la normatividad 17,18 .…”
unclassified